Transformations and permanence of the man-father in the care of the newborn, in rooming-in (Research, Society and Development, 2023)
The objective of this study was to recognize the changes and continuities of the father's role in caring for newborns in rooming-in care. A descriptive qualitative study was conducted with 15 fathers who accompanied their partners in a rooming-in unit of a maternity hospital in the city of Rio de Janeiro. Semi-structured interviews were conducted in October and November of 2022 and thematic analysis was employed. Results indicate that daily care participation, involvement in breastfeeding, and the strengthening of affective ties were identified as changes in the father's role. The focus of care centered on the mother and some legal controversies were identified as unfavorable continuities that hinder active fatherhood. Conclusion: Healthcare professionals should acknowledge and include fathers in the care of their children, contributing to breaking stereotypes and changing social paradigms regarding responsible fatherhood.